Investment under Uncertainty, Heterogeneous Beliefs, and Agency Conflicts - Giat, Yahel; Hackman, Steve T.; Subramanian, Ajay (Review of Financial Studies, 2010)
We develop a structural model to investigate the effects of asymmetric beliefs and agency conflicts on dynamic principal–agent relationships. Optimism has a first-order effect on incentives, investments, and output, which could reconcile the private equity puzzle. Asymmetric beliefs cause optimal contracts to have features consistent with observed venture capital and research and development (R&D) contracts. We derive testable implications for the effects of project characteristics on contractual features. We calibrate our model to data on pharmaceutical R&D projects and show that optimism indeed significantly influences project values. Permanent and transitory components of risk have opposing effects on project values and durations. The Author 2009. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please email: journals.permissions@oxfordjournals.org, Oxford University Press.